Gene Therapy for Cardiovascular Disease: Basic Research and Clinical Prospects - Cao, Genmao; Xuan, Xuezhen; Zhang, Ruijing; Hu, Jie; Dong, Honglin (Frontiers in Cardiovascular Medicine, 2021)
Abstract: In recent years, genetic/gene pathogenic factors have been widely recognized by scholars with the deepening of life science research, accompanied by the rapid development of gene-editing technology. In early years, scientists used homologous recombination technology to establish gene knock-out and gene knock-in animal models, and then appeared the second-generation gene-editing technology ZFNs and TALENs that relied on nucleic acid binding proteins and endonucleases and the third-generation gene-editing technology that functioned through protein–nucleic acids complexes -- CRISPR/Cas9 system. This holds another promise for refractory diseases and genetic diseases. Cardiovascular disease (CVD) has always been the focus of clinical and basic research because of its high incidence and high disability rate, which seriously affects the long-term survival and quality of life of patients. Because some inherited cardiovascular diseases do not respond well to drug and surgical treatment, researchers are trying to use rapidly developing genetic techniques to develop initial attempts. However, there are still significant obstacles to gene therapy for inherited cardiovascular diseases, such as incomplete understanding of the nature of the disease, limitations of genetic technology, or ethical concerns. This review mainly introduces the types and mechanisms of gene-editing techniques, the application of gene therapy in cardiovascular diseases and related basic/clinical research, delivering systems, ethical concerns, and the great application value of gene therapy in cardiovascular diseases (especially single-gene inherited cardiovascular diseases).